Existence of SARS-CoV-2 Entry Molecules in the Oral Cavity - Sakaguchi, Wakako; Kubota, Nobuhisa; Shimizu, Tomoko; Saruta, Juri; Fuchida, Shinya; Kawata, Akira; Yamamoto, Yuko; Sugimoto, Masahiro; Yakeishi, Mayumi; Tsukinoki, Keiichi (International journal of molecular sciences, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) receptor, angiotensin-converting enzyme 2 (ACE2), transmembrane protease serine 2 (TMPRSS2), and furin, which promote entry of the virus into the host cell, have been identified as determinants of SARS-CoV-2 infection. Dorsal tongue and gingiva, saliva, and tongue coating samples were examined to determine the presence of these molecules in the oral cavity. Immunohistochemical analyses showed that ACE2 was expressed in the stratified squamous epithelium of the dorsal tongue and gingiva. TMPRSS2 was strongly expressed in stratified squamous epithelium in the keratinized surface layer and detected in the saliva and tongue coating samples via Western blot. Furin was localized mainly in the lower layer of stratified squamous epithelium and detected in the saliva but not tongue coating. ACE2, TMPRSS2, and furin mRNA expression was observed in taste bud-derived cultured cells, which was similar to the immunofluorescence observations. These data showed that essential molecules for SARS-CoV-2 infection were abundant in the oral cavity. However, the database analysis showed that saliva also contains many protease inhibitors. Therefore, although the oral cavity may be the entry route for SARS-CoV-2, other factors including protease inhibitors in the saliva that inhibit viral entry should be considered.